The upper Albian and lower Cenomanian succession at Kolbay, eastern Mangyshlak (southwest Kazakhstan) - Kennedy, W; King, C; Ward, D (2008)
The Kolbay promontory in southwest Kazakhstan exposes a 90-metre section of shallow-marine, terrigenous clastic upper upper Albian and lower lower Cenomanian sediments. The section is described, and a sedimentological and sequence-stratigraphical interpretation are proposed. The youngest Albian ammonite fauna is referred to the Mortoniceras (Subschloenbachia) perinflatum Zone; it comprises Arrhaphoceras (A.) subtetragonum SPATH, 1928, Callihoplites dorsetensis SPATH, 1928, Lepthoplites gracilis SPATH, 1928, Placenticeras kolbajense (SOKOLOV, 1967) (type locality), Idiohamites dorsetensis SPATH, 1939 and Lechites (L.) moreti BREISTROFFER, 1936. The oldest Cenomanian fauna comes from 60 metres higher in the section, and can be referred to the lower Neostlingoceras carcitanenese Subzone of the lower lower Cenomanian Mantelliceras mantelli Zone. It comprises Placenticeras medias iaticum LUPPOV, 1963, Schloenbachia variam (J. SOWERBY, 1817), Mantelliceras saxbii (SHARPE, 1857), Mantelliceras lymense (SPATH, 1926b) and Algentes ellipticus (MANTELL, 1822). The interval between these two faunas lacks age-diagnostic macrofossils, but the section between 47.5 and 55.2 metres above the base of the sequence has yielded the most diverse shark and ray fauna of late Albian to early Cenomanian age known to us, with isolated teeth representing a total of more than twenty-seven species.